2018
DOI: 10.1186/s41065-018-0062-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel RASA1 mutation causing capillary malformation-arteriovenous malformation (CM-AVM): the first genetic clinical report in East Asia

Abstract: Capillary malformation-arteriovenous malformation (CM-AVM) is a clinical entity newly identified in 2003 that is caused by mutation of the RASA-1 gene, which encodes the protein p120-RasGAP. To date, most of the clinical reports on CM-AVM in the literature involve samples entirely consisting of Caucasians of European and North American descent, while reports from China or East Asia are few. Here, we describe a genetic clinical report of CM-AVM. Sequencing revealed a novel stop mutation in the RASA-1 gene causi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…Typical CM lesions are single to multiple, round to oval shape, pinkish to purplish-red or reddish-brown macules with a perilesional pale halo located on the skin and rarely on the mucous membranes. 5 , 10 Less frequently, pinpoint reddish telangiectasia-like papules as in our patients' presentation are also reported. 11 These telangiectasias are found mostly in CM-AVM2, resembling the clinical pictures of hereditary hemorrhagic telangiectasia.…”
Section: Discussionsupporting
confidence: 71%
“…Typical CM lesions are single to multiple, round to oval shape, pinkish to purplish-red or reddish-brown macules with a perilesional pale halo located on the skin and rarely on the mucous membranes. 5 , 10 Less frequently, pinpoint reddish telangiectasia-like papules as in our patients' presentation are also reported. 11 These telangiectasias are found mostly in CM-AVM2, resembling the clinical pictures of hereditary hemorrhagic telangiectasia.…”
Section: Discussionsupporting
confidence: 71%
“…The mutations in RASA1 were first identified in familial PWS patients with AVM by Eerola et al [59,60]. RASA1 mutations have been documented in families with many other vascular malformations, including AVM, SWS, KTS and Parker-Weber syndrome [59,72,73], which suggests that the germline mutations-conferred inherited susceptibility to congenital vascular malformations. RASA-1 encodes for p120-RasGTP-activating protein (p120-RasGAP), a negative regulator to convert Ras to its GDP-bound form by promoting GTP hydrolysis via its C-terminal catalytic domain [74].…”
Section: Pathogenesis Of Pws/swsmentioning
confidence: 99%
“…The p120-RasGAP domain participates in protein-protein interactions with Akt, Aurora or RhoGAP, involving signaling regulating the proliferation, migration, and survival of a variety cell types, including vascular endothelial cells [74]. These mutations are usually deletions in the reading frame or mutations in the catalytic domain [59,72,73], which cause a frame shift or premature termination of RASA1 translation, resulting in a truncated protein with inactivation of the RasGAP domain [59]. The homozygous RASA-1 −/− mouse is lethal; litters dies at E10.5 from the development defects of vascular system and neuronal apoptosis [75].…”
Section: Pathogenesis Of Pws/swsmentioning
confidence: 99%
“…Since Eerola et al first characterized CM-AVM in 2003 [40], extensive reports have associated RASA1 mutations with CM-AVM1 [30,[41][42][43][44][45][46][47], as well as with isolated CM [48][49][50][51] and AVM [52][53][54]. In 2 large scale cohort studies of CM-AVM, RASA1 germline mutations were identified in ∼70% of probands (44 and 68 out of 56 [41] and 100 [30] probands screened, respectively) with a high occurrence of de novo mutations (31.8% [41] and 26.5% [30], respectively), highlighting the high prevalence of RASA1 mutation in CM-AVM cases as well as the importance of using a trio-family design to identify mutations with various inheritance models.…”
Section: Rasa1 Human Diseasesmentioning
confidence: 99%